Whole-Genome Sequencing of Two Latin American–Mediterranean Extensively Drug-Resistant Mycobacterium tuberculosis Clinical Isolates from Medellín, Colombia - Alvarez, N. (Genome Announc, 2016)
Colombia, with a tuberculosis incidence of 33 cases per 100,000 population, is one of the countries that have reported extensively drug-resistant Mycobacterium tuberculosis (XDR-TB). We report the high-quality draft genome sequences of two Latin American–Mediterranean XDR-TB clinical isolates (TBR-152 and TBR-175), comprising 4,303,775 bp and 4,330,115 bp, respectively.